The manufacture of transit. Border control, urban trends and migrant trajectories in Nouadhibou (Mauritania) - (:unkn) unknown (My University, 2012)
This chapter examines different forms of migrant integration in Nouadhibou, Mauritania. In this town, the activities developed by transit migrants have been integrated in the local economic network, which is largely articulated around the activities of waves of earlier migrants that have been instilled with a renewed dynamism by newcomers. Since the implementation of border surveillance measures in 2006, transit migration has been identified as the target of specific (police and humanitarian) practices assigned to specific actors. Within a matter of years, these mechanisms have produced an entirely new universe of people, practices, places, and technologies gravitating around "illegal" migration, and have also highlighted the situation of presumed "illegals" (either by stigmatizing them or by defending them). As a category of migration management developed in expert discourses, "transit migration" has produced the category of "transit" migrants, thus spelling the end of a conception of migration in which transitory residence was just one feature among others of migrant presence within the town.
Keywords: African Research